2020
DOI: 10.1038/s41598-020-70060-8
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting low flow conditions months in advance through teleconnection patterns, with a special focus on summer 2018

Abstract: Over the past decades, Europe has been affected by several low flow periods which had substantial impacts on the hydrology of the rivers themselves as well as on the society and economy. Low flow periods have a direct impact on the environment, on the inland waterway navigation, on the hydropower production as well as on the sediment management, among others. Similar to floods, low flows are naturally occurring phenomena which can significantly hinder different uses and functions of the rivers and impact the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…Previous work shows many of these areas to have weak to moderate, yet often significant, NAOI‐P correlations; such as for western and northern England (West et al, 2019), northern Germany (Riaz et al, 2017), southern France (Massei et al, 2007). Indeed, many studies in these regions have found skilful prediction of winter rainfall (and other water resource variables) through use of the historical NAOI‐P relationship, despite the non‐stationary reported here (Ionita & Nagavciuc, 2020; Moreira et al, 2016; Rasouli et al, 2020; Rousi et al, 2020; Scaife et al, 2014; Svensson et al, 2015). This apparent contradiction with our non‐stationary correlation results at decadal timescales and results from other studies for multi‐decadal timescales (Pauling et al, 2006; Vicente‐Serrano & López‐Moreno, 2008) can be explained by the common multi‐decadal periods of relative stability in our results, despite general non‐stationarity throughout the rolling correlation series.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous work shows many of these areas to have weak to moderate, yet often significant, NAOI‐P correlations; such as for western and northern England (West et al, 2019), northern Germany (Riaz et al, 2017), southern France (Massei et al, 2007). Indeed, many studies in these regions have found skilful prediction of winter rainfall (and other water resource variables) through use of the historical NAOI‐P relationship, despite the non‐stationary reported here (Ionita & Nagavciuc, 2020; Moreira et al, 2016; Rasouli et al, 2020; Rousi et al, 2020; Scaife et al, 2014; Svensson et al, 2015). This apparent contradiction with our non‐stationary correlation results at decadal timescales and results from other studies for multi‐decadal timescales (Pauling et al, 2006; Vicente‐Serrano & López‐Moreno, 2008) can be explained by the common multi‐decadal periods of relative stability in our results, despite general non‐stationarity throughout the rolling correlation series.…”
Section: Discussionmentioning
confidence: 62%
“…Some forecasting systems seek to project further into the future to allow long‐term planning of infrastructure and resilience to extremes and climate change (Svensson et al, 2015). These systems can rely directly or indirectly on outputs from Global Climate Models (GCMs; such as gridded reanalysis datasets) to forecast hydrological conditions (Bhatt & Mall, 2015; Ionita & Nagavciuc, 2020). In the North Atlantic region, in particular Western Europe, the North Atlantic Oscillation (NAO) is used as an indicator for hydrometeorological conditions given its leading control on winter rainfall totals (Hurrell & Deser, 2010; Scaife et al, 2008, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The rainfall deficit and the high temperatures over the last decade have also led to extremely low river flows. Some of the most important waterways in Europe have been seriously affected, with enormous economic consequences 14 . April 2020, the driest of the last 140 years, has set a new record for low flows in the Elbe River (north-eastern part of Germany) ( Fig.…”
Section: Central European Hydroclimate Over the Last Decadementioning
confidence: 99%
“…Droughts, which can extend over large areas and last for several years, are amongst the most damaging and expensive natural hazards. Since the beginning of the 21st century, Europe has experienced a series of prolonged summer heatwaves and droughts (e.g., 2003,2010,2013,2015,2018,2019), associated with substantial environmental damage and financial and human losses [9][10][11][12][13][14] . For example, the financial losses due to the 2018 drought were estimated to be~3.3 billion EUR, which made it the costliest single-year event in Europe 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation